Improving weld accuracy and reducing production time through fixture-assisted TIG welding - Abu Bakar, Mohd Haziq Asyraaf; Zulkefli, Nursyazwani; Ahmad, Aida Husna; Osman, Saliza Azlina; Tay, Sin Kiat; Osman, Shahrul Azmir (UiTM Press, 2025)
Welding quality is a critical determinant of structural integrity and production efficiency in precision manufacturing. However, conventional steel frame fabrication processes often suffer from inconsistencies, dimensional inaccuracies, and extended setup durations due to the lack of standardized welding fixtures. This research investigates the influence of welding jig design on manufacturing performance and dimensional accuracy through a comparative analysis of conventional and jig-assisted welding methods. A case study approach was employed, integrating stopwatch time study techniques and quality assessment protocols to quantify productivity and precision improvements. Experimental procedures evaluated five complete fabrication cycles for each method using Westinghouse performance ratings, element-based time recording, and Coordinate Measuring Machine (CMM) distortion measurements across nine critical points. The findings indicate that the application of welding jigs substantially enhances process efficiency and product quality. Total fabrication time decreased from approximately 25.8 hours to 19.9 hours per frame, achieving a 23% improvement in productivity. Dimensional compliance increased from 75% to over 90% of measurements within specified tolerances. The most significant time savings were observed in primary welding operations, where setup and alignment tasks were minimized. These results provide empirical evidence that jig-assisted welding improves operational consistency, reduces operator dependency, and strengthens quality control in precision manufacturing. The study concludes that welding jigs represent a viable solution for achieving an optimal balance between efficiency and accuracy, supporting datadriven investment decisions in fixture development and process standardization within modern fabrication industries.